2015
DOI: 10.1037/fsh0000134
|View full text |Cite
|
Sign up to set email alerts
|

Health disparities among youth with type 1 diabetes: A systematic review of the current literature.

Abstract: Findings from our review suggest an association between race/ethnicity, SES, and health outcomes in pediatric T1D. Researchers should consider developing interventions that take into account factors which may place children from racial/ethnic minority and lower-SES backgrounds at risk for poor metabolic control and emotional functioning. Future research should examine causative mechanisms of health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 61 publications
5
68
2
Order By: Relevance
“…Thus, in a previous review on a similar topic, more homogeneous results were found showing that in 18 studies adolescents with a lower socio‐economic status had higher HbA 1c levels than adolescents with a higher socio‐economic status, and in three further studies young people with lower socio‐economic status experienced more acute complications compared with those with higher socio‐economic status. But in this review, the authors did not distinguish between the different indicators of socio‐economic status .…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in a previous review on a similar topic, more homogeneous results were found showing that in 18 studies adolescents with a lower socio‐economic status had higher HbA 1c levels than adolescents with a higher socio‐economic status, and in three further studies young people with lower socio‐economic status experienced more acute complications compared with those with higher socio‐economic status. But in this review, the authors did not distinguish between the different indicators of socio‐economic status .…”
Section: Discussionmentioning
confidence: 93%
“…Notably, we show that causal-biochemical knowledge mediates the negative effect of low family income on glycaemic control. The impact of family-related risk factors on HbA1c levels was shown in several studies; factors such as single-parent family, low socioeconomic status, non-Caucasian ethnicity and family conflicts were previously found to be correlated with poor glycaemic control and high serum levels of HbA1c (Borschuk & Everhart, 2015;Gomes & Negrato, 2016;Lewin et al, 2006;Mazarello Paes et al, 2018;Stahl-Pehe et al, 2017). Although low family income was significantly associated with high HbA1c levels in our bivariate analyses and in the hierarchical model, when analysed by the mediation model, causal-biochemical knowledge blurred its significance, whereas T1DM self-management knowledge did not.…”
Section: Discussionmentioning
confidence: 97%
“…18 Meanwhile, lower socioeconomic status has been associated with higher post-discharge mortality among elderly patients. 19 While social determinants such as education, race, and income have been associated with disease development and outcomes, [19][20][21][22] they are also intricately associated with each other as well as additional social determinants, health behaviors, and medical comorbidities. [23][24][25] Thus, the causality of a single social determinant on disease outcome is difficult to identify but rather several social determinants often work together to influence disease development.…”
Section: Discussionmentioning
confidence: 99%